Moving towards action : anti-racism in leadership learning - Beatty, Cameron C.; Manning-Ouellette, Amber (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"Moving Towards Action: Centering Anti-Racism in Leadership Learning speaks to communities of people within and surrounding higher education and specifically, leadership educators, partners, researchers, administrators, and student affairs practitioners. The text expands thinking on the concepts of socially and racially just leadership education by unpacking the ways in which individual, structural, and systemic racism can be embedded in curricular, co-curricular, community-based, and unstructured leadership courses and programs. By centering how implicit and explicit racism are woven into leadership education, the text asks leadership educators to critically explore their own anti-racist approaches, reimagine their leadership program outcomes, and think more broadly about how leadership education can be more anti-racist and move towards action with equitable and just outcomes. Beatty and Manning-Ouellette assemble the text for all audiences to gain a deeper, more complex perspective on racism, anti-racist frameworks, and leaving leadership education better than when they arrived. The text is organized in such a way that leadership educators can take away new practices for navigating personal struggle, fragility, and resistance around topics of racism that occur in both curricular and co-curricular collegiate leadership programs. Beatty and Manning-Ouellette arrange the text in three sections: 1. Theoretical and Conceptual Considerations of Anti-Racism Approaches to Leadership Learning, 2. Innovations in Research & Practice, and 3. Moving Towards Action with contributions from leadership educators and scholars. Therefore, the text serves as an entry point to dialogue, think, and coalesce about anti-racism in leadership learning and explore what possibilities exist for us to move toward anti-racist praxis and pedagogy in leadership education"-- Provided by publisher.
Keywords: Leadership -- Study and teaching.; Leadership -- Moral and ethical aspects.; Racism.; Anti-racism.; Education -- Leadership.; Racism and racial discrimination, Anti-racism.; Educational strategies and policy.; elektronické knihy; electronic books